DEVELOPMENT OF REGULATORY IMPACT INSTITUTE UNDER DIGITIZATION PROCESS: EXPERIENCE OF RUSSIA AND KAZAKHSTAN - Turgel Irina Dmitrievna; Panzabekova Axana Zhakitzhanovna; Symaniuk Nina Vasilyievna (Scientific Journal of Pedagogy and Economics, 2019)
The goal of the research is comparative analysis of approaches to regulatory impact assessment institute development under the digitization process in the largest post-Soviet countries – Russia and Kazakhstan, characteristics of digital technologies influence on the institute development in the countries of analyzed integrity. The research was conducted using general scientific and special methods. The general scientific of comparative and evolution-genetic investigations were used for cross-national comparison of processes on implanting new governmental institutes in historical retrospective. The specialized methods of institutional and constitutional theory allowed analyzing the mutual influence of legislative and economic factors at making the governmental decisions in the field of digitization of regulatory policy within the settled national systems of public administration. The digitization priorities of the public administration system in Russia and Kazakhstan and settled vision of the regulatory impact assessment institute modification under new conditions were characterized. The common and specific features in approaches implemented by these countries to assessment institute digitization were revealed. The functions, structure and content of the official Internet portals used for arrangement of rule-making process were compared as well as organizational ways of acquisition and collection of information characterizing the activity in the field of regulatory impact assessment. The results of the research can be used by the national authorities of Russia and Kazakhstan, supranational structures of the Eurasian Economic Union to justify the most effective ways of digitization of the regulatory impact assessment institute, by specialists in the field of comparative investigations to broaden the perception on developing new institutes of public administration under digitization process. By the research results the prospective digitization development trends for the regulatory impact assessment institute were suggested for the analyzing countries.